Current trends in the development of distance learning - Solovyova, O.; Соловйова, Ольга Володимирівна (Харківський національний автомобільно-дорожній університет, 2022)
For the past two decades, there has been a transition from traditional to online learning. This became possible mostly with the development of the Internet, which made it possible to send the required number of information from one end of the world to another, freely discuss with other users online and post information on Internet sites, making it available to anyone. Modern information technologies make it possible to increase and improve the efficiency of the educational process. During the reform of education in higher education institutions, the concept of distance education is progressively developed, which provides for the development of various technologies, including blended learning technologies.
Keywords: online learning; distance learning